3 - La coopération économique afro-arabe: Nécessité d’une Longue Haleine - Bernard FOUNOU-TCHVIGOUA (Africa Development, 1986)
There is hardly any Afro-Arab economic cooperation in spite of the fact that in the present world economic crisis period financial flows have developed especially under the form of preferential loans made out by Arab States to African countries. Yet for historical, geographical, cultural and even political reasons, the development of both groups of states requires that they cooperate. However obstacles - some of which are common to the South-South cooperation in general - are not to be minimized. These common obstacles include the cooperation policy of countries at the Center, directed for a large part against the South; anti-South protectionnist practices which can be observed in the very "South"; the system's capacity to grab concepts developed in national and popular self-centered development theories, which reflects the ideological confusion of the bourgeoisie in the "South". There are also specific obstacles one of which is the asymetry in relationships since the expansion of Islam and the Arab culture.